Case report: Coronary allograft vasculopathy: an accurate reflection of the histopathological findings on cardiovascular magnetic resonance imaging - Napolitano, Carmela; Grutter, Giorgia; Francalanci, Paola; Amodeo, Antonio; Secinaro, Aurelio (Frontiers in Cardiovascular Medicine, 2023)
Heart transplant recipients undergo extensive invasive and non-invasive postoperative screening to exclude complications, such as allograft rejection and vasculopathy. Cardiac magnetic resonance imaging is a non-invasive, non-irradiating, diagnostic tool for monitoring graft health and identifying possible tissue rejection or myocardial fibrosis. We describe the case of a 29-year-old female heart transplant recipient admitted to our care center with a worsening clinical condition. The patient underwent clinical evaluation, blood tests, including troponin I and N-terminal pro brain type natriuretic peptide, transthoracic echocardiography, invasive coronary angiography, and cardiovascular magnetic resonance imaging. Cardiovascular magnetic resonance imaging showed widespread sub-epicardial hyperintensity of the myocardial segments along the course of the coronary arteries. T2 mapping sequences showed an elevated value and the myocardial native T1 values and extracellular volume percentage were significantly increased. Late gadolinium enhancement demonstrated a diffuse sub-epicardial hypersignal along the lateral, free, and left ventricular walls. All the sequences evidenced widespread hyper-enhancement of epicardial fat along the course of the thickened main coronary artery walls. One month later, the recipient underwent re-transplantation due to progressive worsening of the clinical condition and refractoriness to intravenous medication. The anatomopathological findings of the explanted heart provided impressive visualization of structural and histopathological changes. These results could guide the tailoring of preventive therapeutic strategies and non-invasive monitoring of cardiac grafts.